Spontaneous extrusion of a dexamethasone intravitreal implant (Ozurdex) - Ong, Jessica (BMJ Case Rep, 2020)
A 59-year-old man with diabetic macular oedema was treated with a dexamethasone intravitreal implant (Ozurdex) to his right eye. Immediately after injection, the implant was noted to have extruded into the perilimbal subconjunctival space. The remnants of the implant were expeditiously removed the following day to avoid corneal decompensation and permanent corneal oedema. Endothelial decompensation secondary to the migration of dexamethasone implants into the subconjunctival space or anterior chamber is a recognised complication of Ozurdex injection. The patient recovered well postoperatively with no further complications. He was planned for a new Ozurdex implant 1 month later.